Time to redefine PD? Introductory statement of the MDS Task Force on the definition of Parkinson's disease. Issue 4 (11th March 2014) - Berg, Daniela; Postuma, Ronald B.; Bloem, Bastiaan; Chan, Piu; Dubois, Bruno; Gasser, Thomas; Goetz, Christopher G.; Halliday, Glenda M.; Hardy, John; Lang, Anthony E.; Litvan, Irene; Marek, Kenneth; et al.
ABSTRACT With advances in knowledge disease, boundaries may change. Occasionally, these changes are of such a magnitude that they require redefinition of the disease. In recognition of the profound changes in our understanding of Parkinson's disease (PD), the International Parkinson and Movement Disorders Society (MDS) commissioned a task force to consider a redefinition of PD. This review is a discussion article, intended as the introductory statement of the task force. Several critical issues were identified that challenge current PD definitions. First, new findings challenge the central role of the classical pathologic criteria as the arbiter of diagnosis, notably genetic cases without synuclein deposition, the high prevalence of incidental Lewy body (LB) deposition, and the nonmotor prodrome of PD. It remains unclear, however, whether these challenges merit a change in the pathologic gold standard, especially considering the limitations of alternate gold standards. Second, the increasing recognition of dementia in PD challenges the distinction between diffuse LB disease and PD. Consideration might be given to removing dementia as an exclusion criterion for PD diagnosis. Third, there is increasing recognition of disease heterogeneity, suggesting that PD subtypes should be formally identified; however, current subtype classifications may not be sufficiently robust to warrant formal delineation. Fourth, the recognition of a nonmotor prodrome of PD requires that new diagnostic criteria for early‐stage and prodromal PD should be created; here, essential features of these criteria are proposed. Finally, there is a need to create new MDS diagnostic criteria that take these changes in disease definition into consideration. © 2014 International Parkinson and Movement Disorder Society